Urbanisation and environmental degradation in Dhaka Metropolitan Area of Bangladesh. (1st January 2012) - Dewan, Ashraf M.; Kabir, Md. Humayun; Nahar, Kamrun; Rahman, Md. Ziaur
Using available data on relevant issues and onsite field visits, this paper documented the environmental problems associated with the unprecedented urbanization in Dhaka Metropolitan Area of Bangladesh. Analyses revealed that a rapid spatial expansion of the city has been taking place alongside the remarkable rise in urban population, simultaneously putting immense pressure on natural resource-base. Substantial changes that were observed in land use and cover are believed to be a significant factor in elevating the risk of natural hazards, particularly flooding during monsoon. In addition, air, water, and noise quality, have all become acute, and are subsequently posing uncertain liabilities to the inhabitants' health of the area. Rapid uncoordinated urbanisation gives rise to a spectacular growth of slums and squatters, making 3.4 million slum dwellers in 2006 from only 1.5 million in 1996. Achieving sustainable urban development in the DMA therefore, requires tackling the environmental problems in a rational manner.